Optimizing the Pd Sites in Pure Metallic Aerogels for Efficient Electrocatalytic H2O2 Production. Issue 14 (2nd March 2023) - Zhang, Xin; Wang, Cui; Chen, Kai; Clark, Adam H.; Hübner, René; Zhan, Jinhua; Zhang, Liang; Eychmüller, Alexander; Cai, Bin
Abstract : Decentralized electrochemical production of hydrogen peroxide (H2 O2 ) is an attractive alternative to the industrial anthraquinone process, the application of which is hindered by the lack of high‐performance electrocatalysts in acidic media. Herein, a novel catalyst design strategy is reported to optimize the Pd sites in pure metallic aerogels by tuning their geometric environments and electronic structures. By increasing the Hg content in the Pd–Hg aerogels, the PdPd coordination is gradually diminished, resulting in isolated, single‐atom‐like Pd motifs in the Pd2 Hg5 aerogel. Further heterometal doping leads to a series of M–Pd2 Hg5 aerogels with an unalterable geometric environment, allowing for sole investigation of the electronic effects. Combining theoretical and experimental analyses, a volcano relationship is obtained for the M–Pd2 Hg5 aerogels, demonstrating an effective tunability of the electronic structure of the Pd active sites. The optimized Au–Pd2 Hg5 aerogel exhibits an outstanding H2 O2 selectivity of 92.8% as well as transferred electron numbers of ≈2.1 in the potential range of 0.0–0.4 VRHE . This work opens a door for designing metallic aerogel electrocatalysts for H2 O2 production and highlights the importance of electronic effects in tuning electrocatalytic performances. Abstract : X. Zhang, C. Wang, K. Chen, A. H. Clark, R. Hübner, J. Zhan, L. Zhang, A. Eychmüller, B. Cai A novel catalyst design strategy is demonstrated for the optimization of Pd sites in pure metallic aerogels by tuning their geometric environments and electronic structures. By diminishing the PdPd coordination, single‐atom‐like Pd motifs are constructed in the Pd2 Hg5 aerogel, which are further fine‐tuned to achieve an excellent electrocatalytic activity and selectivity for hydrogen peroxide (H2 O2 ) production.